EVALUASI SIKAP KONSUMEN TERHADAP PERLUASAN MEREK SAKATONIK LIVER KE SAKATAONIK ABC - , Retno Susilo Wardani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A strong brand is a company's asset which can be used as a shortcut to enter new markets through brand extension. Brand extension strategy is chosen to reduce the cost of new product introduction, transferring awareness and association of brands of origin to the new product extension. The purpose of this study is to evaluate consumersâ attitude towards the brand extension of Sakatonik Liver to Sakatonik ABC. There are four hypothesis evaluated in this research: brand knowledge (H1), perceived quality (H2), perceived fit (H3), and perceived level of difficulty a company has to undergo when making a brand extension (H4)